Effects of a single dose of dietary nitrate via beetroot crystals on high-intensity intermittent exercise performance in recreational collegiate athletes - Saleh, Maisarah Mohd; Dev, Roxana Dev Omar; Linoby, Adam; Norhamazi, Iqbal; Ab Raza, Rozella; Sulaiman, Norhasmah; Jaapar, Salimah (DJ Studio, 2024)
Endurance and high-intensity intermittent exercise are paramount in the pursuit of optimal athletic performance. Nitrate (NO3 −) supplementation has emerged as a promising avenue for enhancing these aspects. Prior studies underscore the beneficial role of nitrate supplementation in augmenting endurance and high-intensity intermittent exercise. The current study probes the immediate effects of nitrate supplementation, specifically beetroot crystals (BRC), on high-intensity intermittent running performance in recreational collegiate athletes. In a randomized, cross-over, placebo-controlled, double-blind investigation, fourteen male athletes consumed either an acute dose of BRC (25 g·day−1, containing ~8.1 mmol of NO3 −) or a placebo (PLA; 25 g·day−1 of maltodextrin) 1.5 hours prior to undergoing a highintensity intermittent exercise test in a controlled laboratory setting. Results elucidated that BRC supplementation improved high-intensity intermittent exercise performance (BRC: 270.5 ± 138.5 s vs. PLA: 231.7 ± 141.5 s; p < 0.05) and elevated plasma plasma NO3 − and NO2 − concentrations compared to the placebo group (p < 0.05). Nonetheless, blood pressure, muscle oxygenation, plasma lactate, and glucose levels did not reveal any significant differences (p > 0.05). Crucially, this study stands as the first to identify BRC as a significant enhancer of intermittent cycling performance in a controlled laboratory setting. These findings underscore the potential of acute BRC supplementation in boosting high-intensity intermittent exercise performance in recreational collegiate athletes, thereby prompting further investigation into its potential usage in sports and exercise scenarios.